Implementation of a multicomponent intervention to optimise patient safety through improved oxygen prescription in a rural hospital. (December 2014) - Gunathilake, Roshan; Lowe, Deborah; Wills, James; Knight, Anne; Braude, Peter
Abstract Objective To rationalise oxygen procedures in adult medical and surgical inpatients with a view to improving patient safety. Design Prospective pre‐ and post‐intervention audit. Setting Manning Hospital, a rural referral hospital in Taree NSW. Participants Pre‐intervention: 82 patients aged 72.7 ± 14.7 years. Post‐intervention: 77 patients aged 73.6 ± 12.4 years. Intervention A multicomponent intervention composed of implementation of a local hospital oxygen policy, introduction of a specific oxygen prescription chart and targeted staff education. Main outcome measures Satisfactory oxygen prescription, monitoring and titration. Results Only 2/82 (2.4%) patients had satisfactory oxygen prescription specifying target saturation, device and initial flow rate before the intervention compared with 26/77 (34%) patients post‐intervention (χ2 = 56.88, df = 5, P < 0.0001). Percentage of patients with conditions predisposing to hypercapnic respiratory failure who were overtreated with oxygen dropped from 9/19 (47%) to 4/22 (18%) following the study intervention (χ2 = 4.011, df = 1, P = 0.04). Oxygen therapy monitoring was satisfactory during the audit period, but oxygen titration was unsatisfactory and did not significantly improve following the intervention. Conclusions A multicomponent intervention can achieve a significantly increased rate of satisfactory oxygen prescriptions specifying target saturation, including in those who are at risk of hypercapnic respiratory failure.